2023
DOI: 10.3390/jcm12041246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acetazolamide on Postural Control in Patients with COPD Travelling to 3100 m Randomized Trial

Abstract: Patients with chronic obstructive pulmonary disease (COPD) may be susceptible to impairments in postural control (PC) when exposed to hypoxia at high altitude. This randomized, placebo-controlled, double-blind, parallel-design trial evaluated the effect of preventive acetazolamide treatment on PC in lowlanders with COPD traveling to 3100 m. 127 lowlanders (85 men, 42 women) with moderate to severe COPD, aged 57 ± 8 y, living below 800 m, were randomized to treatment with acetazolamide 375 mg/d starting 24 h be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…In the current study, the altitude-induced alteration in postural control was mainly reflected in a longer COPL that was related to an increased AP sway velocity and amplitude. These observations are consistent with previous studies, which also showed that altitude exposure increased the sway in anterior-posterior direction (Muralt et al, 2018;Buergin et al, 2023). It has been suggested that this may be due to the anatomical alignment of the leg and feet joints that result in a greater flexibility in the antero-posterior compared to the medio-lateral direction and to the greater sensitivity of the visual corrective input to lateral vs. antero-posterior alterations (Nordahl et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the current study, the altitude-induced alteration in postural control was mainly reflected in a longer COPL that was related to an increased AP sway velocity and amplitude. These observations are consistent with previous studies, which also showed that altitude exposure increased the sway in anterior-posterior direction (Muralt et al, 2018;Buergin et al, 2023). It has been suggested that this may be due to the anatomical alignment of the leg and feet joints that result in a greater flexibility in the antero-posterior compared to the medio-lateral direction and to the greater sensitivity of the visual corrective input to lateral vs. antero-posterior alterations (Nordahl et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Our data suggest that older age within this range had a negative effect on AP sway velocity while the COPL and mediolateral sway velocity were not associated with age (Tables 3, 4). A worse postural control of older compared to younger mountaineers has been reported previously (Bruyneel et al, 2017;Buergin et al, 2023). Moreover, a large-scale study has shown that postural control deteriorates with increasing age even at sea level (Era et al, 2006).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations